Dietary Interventions for Atopic Disorders - Mavrommati, Despoina; C. Theoharides, Theoharis (Current Pharmaceutical Design, 2014)
There are a number of atopic conditions that involve mast cells ranging from common allergies to arthritis and chronic pelvic pain syndrome. In addition to the well known allergic triggers, many food substances, drugs, as well as physical and mental stressful conditions could trigger mast cell activation in the absence of any allergic diathesis. The chronicity and morbidity of these conditions and the concern for the “adverse side effects” of the available therapeutic agents has prompted the widespread use of complementary and alternative medicines (CAM). One of the most common CAM interventions in the treatment of allergies is the use of dietary supplements that may contain specific compounds such as chondroitin sulfate, bioflavonoids or various herb extracts including Forsythia, Gingko, and Echinacea. The basis of such use has evolved from clinical anecdotal observations over time, to a growing number of in vitro and some in vivo studies that support the use of some of these compounds, especially select flavonoids.
Keywords: flavonoids